2015
DOI: 10.3758/s13428-015-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

Tap Arduino: An Arduino microcontroller for low-latency auditory feedback in sensorimotor synchronization experiments

Abstract: Timing abilities are often measured by having participants tap their finger along with a metronome and presenting tap-triggered auditory feedback. These experiments predominantly use electronic percussion pads combined with software (e.g., FTAP or Max/MSP) that records responses and delivers auditory feedback. However, these setups involve unknown latencies between tap onset and auditory feedback and can sometimes miss responses or record multiple, superfluous responses for a single tap. These issues may disto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 19 publications
(29 reference statements)
0
53
0
Order By: Relevance
“…Arduino open-source microcontroller platform was used (https:// www.arduino.cc/). Several studies have shown that the Arduino is able to measure signals with less than 1 ms variability (D'Ausilio, 2012;Schubert, D'Ausilio, & Canto, 2013;Schultz & van Vugt, 2016), making it an ideal low-cost lab equipment. Several studies have shown that the Arduino is able to measure signals with less than 1 ms variability (D'Ausilio, 2012;Schubert, D'Ausilio, & Canto, 2013;Schultz & van Vugt, 2016), making it an ideal low-cost lab equipment.…”
Section: Mood Ratingmentioning
confidence: 99%
See 1 more Smart Citation
“…Arduino open-source microcontroller platform was used (https:// www.arduino.cc/). Several studies have shown that the Arduino is able to measure signals with less than 1 ms variability (D'Ausilio, 2012;Schubert, D'Ausilio, & Canto, 2013;Schultz & van Vugt, 2016), making it an ideal low-cost lab equipment. Several studies have shown that the Arduino is able to measure signals with less than 1 ms variability (D'Ausilio, 2012;Schubert, D'Ausilio, & Canto, 2013;Schultz & van Vugt, 2016), making it an ideal low-cost lab equipment.…”
Section: Mood Ratingmentioning
confidence: 99%
“…The Arduino is an inexpensive, low-level microcontroller which has an excellent temporal resolution owing to its property of bypassing the hardware and software environments of modern operating systems (D'Ausilio, 2012). Several studies have shown that the Arduino is able to measure signals with less than 1 ms variability (D'Ausilio, 2012;Schubert, D'Ausilio, & Canto, 2013;Schultz & van Vugt, 2016), making it an ideal low-cost lab equipment. A customised script allowed for an instantaneous manipulation of pulses at desired theta and gamma frequencies.…”
Section: Mood Ratingmentioning
confidence: 99%
“…An Arduino Leonardo board processed all the signal generation and acquisition internally, to ensure minimal latency [7,26]. For logging, data frames were transmitted to a PC with an internally-generated timestamp attached; thereby, communication latency could be avoided.…”
Section: Apparatusmentioning
confidence: 99%
“…Second, we provided delay measurements for cue stimuli and reinforcement delivery and made significant efforts to minimize these latencies and jitters, achieving submillisecond precision in reinforcement timing. Indeed, very few such measurements has been made available to date (Chen and Li, 2017;D'Ausilio, 2012;Schultz and van Vugt, 2016), and those are mostly restricted to microcontroller board delays or simple cue stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time operating systems can be used to achieve submillisecond behavior control (Brunton et al, 2013;Jaramillo and Zador, 2011;Poddar et al, 2013). However, the emergence of affordable microcontrollers that are easy to program provide a unique opportunity to build modular, flexible and cheap behavior control systems suitable for millisecond order precision (D'Ausilio, 2012;Schultz and van Vugt, 2016).…”
Section: Introductionmentioning
confidence: 99%